Will agricultural digitalization deliver relative advantages in quality of work, productivity, profitability, return on investments, and reliability? Perceptions of Canadian producers - Abdulai, Abdul-Rahim; Pulido-Castanon, Jesus; Duncan, Emily Rose; Ruder, Sarah-Louise; K. C., Krishna Bahadur; Fraser, Evan (Informa UK Limited, 2024)
Digitalization is often claimed by agri-food actors interested in using technology and corporations to provide many socio-economic benefits for farmers. This article reports on the results of a survey of Canadian farmers (n = 852) to explore producer perceptions of whether new digital technologies 1) improve the quality of work, 2) enhance productivity, 3) increase profitability, 4) offer a reliable return on investment, and 5) are as reliable as earlier tools and technologies. Farmer respondents generally agreed that digital farm tools have certain relative advantages, but considerable skepticism and varying views persist for certain benefits. Farmers with experience using digital tools were more likely to agree to improved quality of work and reliable return on investments. Meanwhile, farmer socio-demographics (region, level of education, farm ownership ratio) partly and to varying degrees explain perceptions of some relative advantages (e.g. productivity and reliability) but not others (e.g. profitability). In the context of the findings, we note with caution that farmers’ optimism for the relative advantages of digitalization could lay the foundation for acceptance of and receptivity for these innovations. However, if the goal is to encourage producers to embrace digital innovations widely, targeted programming to increase farmers’ first-hand experiences and research-backed informational programs on the potential benefits of digitalization would be needed.